1999
DOI: 10.1063/1.478474
|View full text |Cite
|
Sign up to set email alerts
|

Benzene trimer and benzene tetramer: Structures and properties determined by the nonempirical model (NEMO) potential calibrated from the CCSD(T) benzene dimer energies

Abstract: The energetics and structure of the benzene trimer and tetramer are investigated with the nonempirical model (NEMO) potential calibrated to high precision by comparison with CCSD(T) benzene dimer energies. From the obtained potential energy surface, possible configurations could be determined and the experimental observed structures could be identified. This potential also reproduces the binding energies and allows for the determination of all intermolecular modes. It could be shown that this potential is ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
79
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 12 publications
12
79
0
1
Order By: Relevance
“…Theoretical studies on the trimer have predicted that the most stable structure has cyclic geometry where three benzenes are arranged so as to form an equilateral triangle. 29,39,48,57,59,63 This structure is consistent with IDSRS results reported by Felker's group. 50,53 Here we shall briefly describe their experimental method since this information is necessary to discuss our results.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…Theoretical studies on the trimer have predicted that the most stable structure has cyclic geometry where three benzenes are arranged so as to form an equilateral triangle. 29,39,48,57,59,63 This structure is consistent with IDSRS results reported by Felker's group. 50,53 Here we shall briefly describe their experimental method since this information is necessary to discuss our results.…”
Section: Introductionsupporting
confidence: 93%
“…Recently Engkvist et al have calculated the stabilization energy of the tetramer in several different structures with a more sophisticated nonempirical model ͑NEMO͒ potential based on coupled-cluster single double triple ͓CCSD͑T͔͒ calculations of the dimer. 59 The most stable structure seems to have a geometry similar to that of van de Waal. On the contrary to these results, an IDSRS study of the tetramer associated with intramolecular modes has suggested that the four benzene sites are inequivalent.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Extensive study of benzene has been carried out as well. Recent interest focused on the structure and properties of benzene clusters (30)(31)(32)(33)(34)(35)(36). Isotopically mixed benzene clusters have been used in the investigation of intermolecular interactions.…”
mentioning
confidence: 99%